Antifungal effects of crude extract and fractions of Euphorbia splendida Mobayena gainst Aspergillus niger, Aspergillus fumigatus, Candida albicans and Candida krusei - Seyed reza Hosseini Doust; Asie Shojaii; Atefe Taghva (Islamic Azad University, 2017)
Significant dropping of infectious disease is owned greatly to antibiotic development industry. Due to prevalence of drug resistance organisms alongside with other problems, scientists are focusing on medicinal plants. Medicinal plants and their antimicrobial components are attractive alternatives for antibiotics. In the present project, the antimicrobial effects of methanolic extract and fractions of aerial parts of Euphorbia splendida Mobayen were evaluated against Aspergillus niger, Aspergillus fumigatus, Candida albicans, and Candida krusei. Euphorbiasplendida samples were transferred to laboratory after confirmation. The plant samples were then shadow dried before being powder. Different extracts and fractions were prepared by standard methods. The extracts and fractions were kept under standard conditions until used. The antifungal assessment was performed by standard agar diffusion methods. The concentration of 1000 mg/ml of each of methanolic, hexanic, chloroformic and aqueous extract inhibitedC. krusei growth (15 mm).Themethanolic extract at 500 mg/ml displayed 15 mm inhibition zone C. albicans plate. The aqueous extract had inhibition zone of 14 mm, in C. albicans culture at 500 mg/ml. The methanolic extract at 500 mg/ml inhibited A. niger (15 mm). Meanwhile, methanolic extract at the same concentration allowed the growth of A. fumigatus only beyond 13 mm zone. we concluded that antifungal activities of total extract and fractions of Euphorbia splendida were considerable and more experiments were beneficial in drug development point of view.